2018
DOI: 10.1038/s41557-018-0157-x
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic activation of unstrained C(aryl)–C(aryl) bonds in 2,2′-biphenols

Abstract: Transition-metal catalysis has emerged as an important means for C-C activation allowing mild and selective transformations. However, the current scope of C-C bonds that can be activated is primarily restricted to either highly strained systems or more polarized C-C bonds. In contrast, catalytic activation of nonpolar and unstrained C-C moieties remains an unmet challenge. Here we report a general approach for catalytic activation of the unstrained C(aryl)-C(aryl) bonds in 2,2’-biphenols. The key is utilizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 37 publications
0
44
0
Order By: Relevance
“…[213,214] In such cases CÀC-linkeda romatic dimers with alkyl or 5-5 linking motifs might be more suitable. [215] Such models are not the focus of this Review as the actual identityo ft he linking motifs in such technical lignins is highly diverse and for al arge part unknown. [52] More analysiso ft echnical lignins is required to guide the synthesis of an ew generation of model compounds for use in the valorization of these recalcitrant lignins.…”
Section: Lignocellulose/ligninfeedstockmentioning
confidence: 99%
“…[213,214] In such cases CÀC-linkeda romatic dimers with alkyl or 5-5 linking motifs might be more suitable. [215] Such models are not the focus of this Review as the actual identityo ft he linking motifs in such technical lignins is highly diverse and for al arge part unknown. [52] More analysiso ft echnical lignins is required to guide the synthesis of an ew generation of model compounds for use in the valorization of these recalcitrant lignins.…”
Section: Lignocellulose/ligninfeedstockmentioning
confidence: 99%
“…Currently, only one successful example for the selective cleavage of C ary C ary bond in 5‐5′ linkage has been documented. Dong and co‐workers recently reported a general approach for the catalytic activation of the unstrained C aryl C aryl bonds in 2,2′‐biphenols over a Rh catalyst (Figure ). The phenol moiety served as a handle to install a phosphonite‐directing group that guided the Rh metal insertion into C aryl C aryl .…”
Section: The Challengesmentioning
confidence: 99%
“…Various methods have been developed for effective cleavage of C-O bonds in both lignin and lignin model compounds [6][7][8][9][10][11][12][13][14]. In comparison with the comprehensive studies of C-O bond cleavage, only a handful of examples were reported for selective C-C bond cleavage in lignin or lignin model compounds due to its higher dissociation energies [15][16][17] than that of C-O bond. Such as in 2015, Klankermayer group [18] reported a selective redox-neutral cleavage of C a -C b in b-O-4 lignin models catalyzed by rutheniumtriphos complexes at 160°C (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%